Lubrication model of a knee prosthesis, with non newtonian fluid and porous rough material - Berli, Marcelo Eduardo (2009)
Tibial component of knee prostheses, made of ultra high molecular weight polyethylene (UHMWPE), experiences a high degree of wear and may be expected to last twelve years on average. In this work, a steady state one-dimensional lubrication model of a knee prosthesis is solved through a nu-merical technique based on the Finite Element Method. The model takes into account a non Newto-nian synovial fluid, its ultra filtration mechanism and the surface roughness of a porous elastic layer on the tibial component. The benefits of a porous compliant material placed at the top of the metallic tibial component are shown taking into account the stiffness and exudation capacity of the material and hyaluronic acid concentration of synovial fluid.